2016
DOI: 10.1002/adma.201604260
|View full text |Cite
|
Sign up to set email alerts
|

Confined Metastable 2‐Line Ferrihydrite for Affordable Point‐of‐Use Arsenic‐Free Drinking Water

Abstract: Arsenic-free drinking water, independent of electrical power and piped water supply, is possible only through advanced and affordable materials with large uptake capacities. Confined metastable 2-line ferrihydrite, stable at ambient temperature, shows continuous arsenic uptake in the presence of other complex species in natural drinking water and an affordable water-purification device is made using the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 28 publications
6
55
0
Order By: Relevance
“…Figure A-a shows a transmission electron microscopy (TEM) image of CM2LF. The image suggests that the material is composed of amorphous particles, in agreement with the literature . To further investigate the morphology of the CM2LF aggregates, transmission electron tomographic reconstruction was performed for CM2LF and its composites with As­(III) and As­(V).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Figure A-a shows a transmission electron microscopy (TEM) image of CM2LF. The image suggests that the material is composed of amorphous particles, in agreement with the literature . To further investigate the morphology of the CM2LF aggregates, transmission electron tomographic reconstruction was performed for CM2LF and its composites with As­(III) and As­(V).…”
Section: Resultssupporting
confidence: 83%
“…The materials, magnetite, ,, and two-line ferrhydrite , nanoparticles embedded into organic matter (chitosan and cellulose) are stable in the pH range of 5–9. Previous spectroscopic (XPS and Mossbauer) studies suggest that phosphate-adsorbed wet magnetite nanoparticles remain as magnetite after drying. ,, Kumar et al studied arsenic-adsorbed CM2LF (in the dry state) using X-ray powder diffraction and electron energy-loss spectroscopy . These studies demonstrated that there is no phase change in two-line ferrihydrite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, FTMC exhibits fast adsorption rate in the range of 1100–1600 mg (g min) −1 , and maximum uptake as high as 1540–1781 mg g −1 for other organic dyes (widely used in printing and dyeing industry) like Congo Red (CR), Eosin Y (EY), Pyrosine B (PB), Acid Blue (AB), and Methyl Blue (MB), which are 120–380 and 8–14 times higher than those of AC, respectively (Figure 4c,d). In addition, FTMC is much better than AC in the adsorption of Cefoperazone Sodium (CS, one widely used broad‐spectrum antibiotics drug), arsenate (As(V)), and arsenite (As(III)) from the aspects of maximum uptake and adsorption rate, and is among the best adsorbents reported . Especially FTMC exhibits stable adsorption capacity to arsenate and arsenite in the pH < 7.0 solution (Figure S13, Supporting Information) and is tolerant to competition of various inorganic anions (Figure S14, Supporting Information).…”
mentioning
confidence: 99%
“…[ 14,15 ] Efforts have been made to remove F − from drinking water using activated alumina, but it is ineffective due to low adsorption capacity and lack of regeneration and reusability without side effects. Activated alumina, [ 16 ] hybrid graphene oxide (GO)‐ferric hydroxide composite, [ 17 ] magnetite‐reduced graphene oxide (M‐rGO) composite, [ 18 ] iron oxide, [ 19 ] functionalized graphene nanosheets, [ 20 ] 3D hybrid graphene‐carbon nanotube‐iron oxide composite, [ 21 ] iron oxyhydroxide‐chitosan composite, [ 22 ] activated carbon, [ 23 ] silicon dioxide, [ 24 ] and cellulose‐based materials [ 6 ] have been used to remove arsenic from water in the recent past. Among the different heavy metals, Pb has also been widely found in drinking water, which is also highly toxic to human health.…”
Section: Introductionmentioning
confidence: 99%